Numerical Investigation on Performance Improvement in Tube Inserted with Delta Winglets on Discrete Right-Angled Triangular Plates - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2017)
Numerical investigations on flow topology and heat transfer behavior in a round tube heat exchanger inserted with Delta Winglets (DW) on Discrete Right-angled Triangular Plates (DRTP) are performed. The influences of DW heights; b/D or BR = 0.05-0.25 and flow directions; DW with V-Downstream (DWVD) and DW with V-Upstream (DWVU), are studied for turbulent flow; Re = 3000-10,000. The finite volume method with SIMPLE algorithm is selected to solve the present problem. The numerical results are presented in terms of flow and heat transfer mechanisms; tangential velocity vector, TKE contour, Nux contour, temperature contour. The heat transfer rate, pressure loss and thermal performance in the test tube are also analyzed in forms of Nusselt number (Nu), friction factor (f) and Thermal Enhancement Factor (TEF), respectively. The results show that the tube inserted with the DW on DRTP can help to improve the heat transfer rate and thermal performance in the heating section due to the DW can generate the vortex flow that disturbs the thermal boundary layer on the tube wall. In range investigates, the maximum heat transfer rate is around 4.5 times above the smooth tube with the TEF around 1.9.
Keywords: Wingtip device; Heat transfer enhancement; Vortex generator; Fluid Dynamics and Vibration Analysis